Private Higher Education in Vietnam and Recent Policy Development - Ly, Phạm; Vladimir, Briller (VNU Journal of Science: Social Sciences and Humanities; Vol 31 No 4, 2015)
Vietnam higher education is experiencing the period of rapid development and growth due to two main reasons: the need of highly skilled workforce for one of the fastest developing economies on the planet and because it was “discovered” that higher education in itself can be a very lucrative business, especially for private institutions.  Those two reasons are frequently conflicting with each other: while the first reason drives quality and accountability, the second reason is driven by quantity and opaque practices.  Many not-for-profit universities are still operating like businesses or privately owned companies where profit is the main target.  In the paper, the authors discuss how those issues are addressed by the policy-makers in Vietnam, and in particular, how higher education policies have been dealing with such important topics as university governance, decision making, accountability, profits and quality.  The higher education policies in Vietnam change frequently but they are still far from being perfect; however, they are improving, and hopefully they will soon be compatible with the world’s best practices. Keywords: Private higher education, Vietnam, educational policy.